God hates : Westboro Baptist Church, American nationalism, and the religious right - Barrett-Fox, Rebecca (University Press of Kansas, 2016)
This book places the theology and activism of Westboro Baptist Church in the context of Amreican religious history and suggests that Westboro Baptist Church's message of of national doom reflects a strand of thought that has always been present in American religion and that remains the source of much of the Religious Rights' rhetoric, which is more threatening the democracy than are the uncivil pickets of Westboro Baptists.